Perlindungan Hak Cipta Atas Potret Seseorang Yang Disebarkan Sebagai Meme - Muh. Aldhyansah Dodhy Putra (JIPRO: Journal of Intellectual Property, 2020)
Technology advances in the Web 2.0 era or the days of 'participative web', have led to the widespread dissemination of information or the impact on copyright infringement. One kind of copyright that is often violated is the portrait, especially since the memes era who made spreading a portrait of someone on social media usually happened. Even though the portrait has been regulated in Act Number 28 Year 2014 concerning Copyright (UUHC) as a creation owned by not only the portrait maker but also the person listed therein. The formulation of the problem in this study are; First, how is copyright protection for someone's portrait as a memes?; Second, how is the responsibility of spreading someone's portrait as a meme? This research belongs to normative legal research. The legal materials used are primary legal materials namely the UUHC, and secondary legal materials obtained through literature review. The approach used is the statutory approach, which examines the UUHC and regulations which have a bearing on the legal issues under study. The conclusions of this research as stated in the research problem form include: First, copyright protection for someone's portrait of memes circulating on social media can be found in the UUHC, namely Article 12 of the UUHC for civil law, and 115 UUHC for crime; Second, the responsibility for spreading someone's portrait as a meme circulating on social media can be accomplished by resolving disputes through alternative settlement, arbitration, or court, namely through a commercial court.